The Role of Cysteine Residues in Catalysis of Phosphoenolpyruvate Carboxykinase from Mycobacterium tuberculosis - Machová, Iva; Hubálek, Martin; Lepšík, Martin; Bednárová, Lucie; Pazderková, Markéta; Kopecký, Vladimír; Snášel, Jan; Dostál, Jiří; Pichová, Iva (PloS one, 2017)
Mycobacterium tuberculosis (MTb), the causative agent of tuberculosis, can persist in macrophages for decades, maintaining its basic metabolic activities. Phosphoenolpyruvate carboxykinase (Pck; EC 4.1.1.32) is a key player in central carbon metabolism regulation. In replicating MTb, Pck is associated with gluconeogenesis, but in non-replicating MTb, it also catalyzes the reverse anaplerotic reaction. Here, we explored the role of selected cysteine residues in function of MTb Pck under different redox conditions. Using mass spectrometry analysis we confirmed formation of S-S bridge between cysteines C391 and C397 localized in the C-terminal subdomain. Molecular dynamics simulations of C391-C397 bridged model indicated local conformation changes needed for formation of the disulfide. Further, we used circular dichroism and Raman spectroscopy to analyze the influence of C391 and C397 mutations on Pck secondary and tertiary structures, and on enzyme activity and specificity. We demonstrate the regulatory role of C391 and C397 that form the S-S bridge and in the reduced form stabilize Pck tertiary structure and conformation for gluconeogenic and anaplerotic reactions.
Keywords: Amino Acid Motifs; mutantní proteiny; Biocatalysis; Enzyme Stability; mutace; Protein Structure, Tertiary; Structure-Activity Relationship; terciární struktura proteinů; cystein; tandemová hmotnostní spektrometrie; aminokyselinové motivy; Amino Acid Sequence; mutageneze cílená; Disulfides; sekundární struktura proteinů; Protein Structure, Secondary; molekulární modely; vztahy mezi strukturou a aktivitou; Models, Molecular; Mutagenesis, Site-Directed; stabilita enzymů; substrátová specifita; kinetika; Substrate Specificity; sekvence aminokyselin; biokatalýza; fosfoenolpyruvátkarboxykinasa (závislá na ATP); Mutation; disulfidy; Tandem Mass Spectrometry; Phosphoenolpyruvate Carboxykinase (ATP); Cysteine; Kinetics; Mutant Proteins; Mycobacterium tuberculosis